Prinsip, Adab Dan Amalan Ratib Al-`Attas Dalam Tarekat `Alawi´yah: Suatu Sorotan Ringkas (Sains Humanika, 2015)
This article intends to explain the background of tarekat Alawiyah, principles, practice of Ratib al-`Attas and manners during performing this act. This Tarekat was founded by al-Faqih Muqaddam Muhammad bin Ali Ba`Alawi (w. 653H), whom was related with prophet s.a.w. sadahs `Alawiyin had been propagating islam through da’wah mission, trade and marriage from the early of 1,400 M throughout the archipelago especially in Indonesia, Brunei, Singapore and Malaysia. The spread of this da’wah by sadahs `Alawiyin has led to the spread of tarekat practice and ratib throughout the archipelago. The practice of Ratib al-`Attas had been introduced by Wali Qutub Habib Umar Abdul Rahman al-`Attas (w. 1072H), passed away at Huraidah, Hadramaut, Yaman. This practice is one of the ratib’s collection available in tarekat `Alawiyah. Recently, practice of Ratib al-`Attas are gaining popularity in the hearts of the Muslim community in preserving psychiatric tarbiyah particularly when it is organized properly in madrasah, mosque, musolla,houses and other location suitable for the said purpose. Practically, this practice can be done either individually or in a group without being restricted by time and particularly this is done during the night. Ratib practices also is an informal process of spiritual education which brings the practitioner closer to Allah S.W.T and obtaining prosperity and security outward and inward, world and hereafter.
Keywords: Tasawuf; tarekat; tarekat Alawiyah; Ratib al-Attas; sadahs Alawiyin and spiritual education